2006
DOI: 10.1152/jn.00051.2005
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Neuronal Mechanisms Underlying Physiological Force Tremor in Steady Muscle Contractions of Humans

Abstract: We present results from a study of the 6-to 12-Hz force tremor in relation to motor unit (MU) firing synchrony. Our experimental observations from 32 subjects, 321 contractions, and 427 recorded MUs reveal that tremor is accompanied by corresponding, in-phase MU rhythms that are additional to the ones at the MU intrinsic firing rates. This rhythmical synchrony is widespread and has a uniform strength that ranges from near zero to very large (MU/MU coherence > 0.50) in different contractions. Both the synchrony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 89 publications
5
87
3
Order By: Relevance
“…That is, rhythmic MU synchronization, e.g., underlying tremor activity, reXects in-phase MU rhythms that are additional to those at the MU intrinsic Wring rates (cf. Christakos et al 2006). Put diVerently, there is not necessarily an entrapment of the Wring rates of individual MUs into the 8-12 Hz rhythm, but MU synchronization, as measured by surface EMG, reXects rhythmic modulation of the total EMG amplitude and suggests rhythmic input.…”
Section: Discussionmentioning
confidence: 99%
“…That is, rhythmic MU synchronization, e.g., underlying tremor activity, reXects in-phase MU rhythms that are additional to those at the MU intrinsic Wring rates (cf. Christakos et al 2006). Put diVerently, there is not necessarily an entrapment of the Wring rates of individual MUs into the 8-12 Hz rhythm, but MU synchronization, as measured by surface EMG, reXects rhythmic modulation of the total EMG amplitude and suggests rhythmic input.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that there are several frequency peaks in the PT (Christakos et al 2006;Elble 1996;Halliday et al 1999;McAuley and Marsden 2000;McAuley et al 1997;Takanokura and Sakamoto 2001;Vaillancourt and Newell 2000). For example, finger tremors show oscillations at 10, 20, and 40 Hz (McAuley et al 1997;Takanokura and Sakamoto 2001;Vaillancourt and Newell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These fluctuations, observed in normal individuals, are known as the physiological tremor (PT). Though fluctuation amplitude has been shown to correlate positively with muscle force (Moritz et al 2005;Taylor et al 2003), the amplitude in the frequency domain is more damped at higher frequencies (Christakos et al 2006;Erimaki and Christakos 1999;Sowman and Türker 2005;Taylor et al 2003). For example, the amplitude of finger force fluctuation was shown to fall off at approximately −30 dB/decade in the squared power spectrum around 10 Hz (approximately between 1 and 30 Hz) (Allum et al 1978;Endo and Kawahara 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations